Analysis of Ship Seaworthiness Factors, Health and Safety Culture, Oversight of Port Authority and Harbor Authority Offices on Shipping Safety: (Study at Tanjung Emas Class I Harbormaster and Port Authority Office) - Ignatius Martan; Pius Memo Gading Agum Gumelar; Andar Sri Sumantri (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2023)
Shipping safety is still a problem faced by sea transportation. Empirical data collected in this study shows the number of transportation accidents and fatalities shows a fluctuating number. This means that shipping safety is still a problem faced by the marine transportation industry in Indonesia. To answer this problem, this research is aimed at knowing the effect of ship's seaworthiness, ship health and safety culture, and supervision of the Harbormaster Office and Port Authority on shipping safety performance which is carried out empirically. Every sailing ship must be in a seaworthy condition so as to ensure safety and security while the ship is sailing. Ship's seaworthiness is also assisted with shipping safety facilities and infrastructure. Occupational health is a state of physical, mental and social well-being that allows every worker to work in a healthy manner with optimal productivity without endangering himself, his family, society and the surrounding environment. Occupational health efforts are efforts to harmonize work capacity, workload and work environment so that every worker can work healthily without endangering himself or the surrounding community, in order to obtain optimal work productivity. The duties and responsibilities of a porter are very important in providing a ship's seaworthiness certificate, sailing permit, safety and security as well as all sea transportation shipping activities in Indonesian waters. Based on the results of research and multiple analysis, the following equations are produced: Y = 1.957 + 0.762 X1 + 0.531 X2 + 0.244 X3 + shows that, Based on empirical data (the results of filling out the questionnaire) and the results of multiple linear regression, it shows that the Shipworthiness variable (X1) has a value t count (10.260) > t table (1.99045) then, H0 is rejected and Ha is accepted. The Health and Safety Culture Variable (X2) has a t count (2.382) > t table (1.99045), so H0 is rejected and Ha is accepted. The Port Authority and Port Authority Supervision Variable (X3) has a value of t count (2.280) > t table (1.99045), then H0 is rejected and Ha is accepted. Thus, the results of the study show that there is a positive and significant influence between Shipworthiness, Health and Safety Culture, Harbormaster Supervision and Port Authority on Shipping Safety